6s+10=s

Simple and best practice solution for 6s+10=s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6s+10=s equation:


Simplifying
6s + 10 = s

Reorder the terms:
10 + 6s = s

Solving
10 + 6s = s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-1s' to each side of the equation.
10 + 6s + -1s = s + -1s

Combine like terms: 6s + -1s = 5s
10 + 5s = s + -1s

Combine like terms: s + -1s = 0
10 + 5s = 0

Add '-10' to each side of the equation.
10 + -10 + 5s = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 5s = 0 + -10
5s = 0 + -10

Combine like terms: 0 + -10 = -10
5s = -10

Divide each side by '5'.
s = -2

Simplifying
s = -2

See similar equations:

| -8+4y=-16 | | 4/(9)w^2-5/3w+1 | | z+27=9 | | 7/10+8/15 | | 2(-2w+5)+2w=46 | | -10+4a=5(-2-8a) | | 20/6x-1=8/14 | | x^2-4x+4=19 | | (5/(2y+4))+2=-(6/(y+2)) | | y=-x^2+9x+3 | | 2x^4-12x^2-32=0 | | 2(x-4)+7=-1 | | 6t+11=8t-12 | | 3ln(6x)=9 | | 2(x+4)-9=5x-3(1+x) | | -4x+6(-3x-1)=-182 | | 6t+11=8-12 | | 8t+14=3t-6 | | X[14]=2 | | -3x+7=4x-21 | | 4(x+1)=2(5x-4) | | 2*3.14*7.8= | | X(2x)=200 | | -3x-7=4x+49 | | -4+9=-3(2y+3) | | y=-0.02x^2+0.8x+37 | | 4x^2-23x-28=0 | | 2(x+3)=3x-3x-1-2x+10 | | 13+n=4 | | n+4n=36 | | 4=-3/2(1)+b | | 4n(2n^3p^2-3np^2+5n)+4p(6n^2p-2np^2+3p)=0 |

Equations solver categories